Performativität in Sprache und Recht - Bülow, Lars; Bung, Jochen; Harnisch, Rüdiger; Wernsmann, Rainer (Sprache und Wissen, 2016)
This compendium offers access to readers interested in the humanities and in social, cultural, and legal studies to a broad and multifaceted exploration of linguistic practices in the legal sciences. A range of scholars from the fields of linguistics and the legal sciences focus on specific performative aspects of the connections between language and the law. Lars Bülow, Jochen Bung, Rüdiger Harnischand Rainer Wernsmann, University of Passau, Germany.